Dancing with Difference Culturally Diverse Dances in Education - Ashley, Linda; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
As the global vicissitudes of migration unfold so does ethnic difference in the classroom, and this book offers a timely examination of teaching about culturally different dances. At a time when the world of dance is, on the one hand, seemingly becoming more like fusion cookery there is another faction promoting isolation and preservation of tradition. How, if at all, may these two worlds co-exist in dance education? Understanding teaching about culturally different dances from postmodern, postcolonial, pluralist and critical perspectives creates an urgent demand to develop relevant pedagogy in dance education. What is required to support dance educators into the next phase of dance education, so as to avoid teaching from within a Eurocentric, creative dance model alone? An ethnographic investigation with teachers in New Zealand lays a foundation for the examination of issues, challenges and opportunities associated with teaching about culturally different dances. Concerns and issues surrounding notions of tradition, innovation, appropriation, interculturalism, social justice and critical pedagogy emerge. Engaging with both practice and theory is a priority in this book, and a nexus model, in which the theoretical fields of critical cultural theory, semiotics, ethnography and anthropology can be activated as teachers teach, is proposed as informing approaches to teaching about culturally different dances. Even though some practical suggestions for teaching are presented, the main concern is to motivate further thinking and research into teaching about dancing with cultural difference. Cover photo: Photo credit: lester de Vere photography ltd. Dancing with Difference (2009). Directed and co-choreographed for AUT University Bachelor of Dance by Linda Ashley with Jonelle Kawana, Yoon-jee Lee, Keneti Muaiava, Aya Nakamura, Siauala Nili, Valance Smith, Sakura Stirling and dancers. Won first prize in the 2009, Viva Eclectika, Aotearoa$1 (Bs Intercultural Dance and Music Biennial Challenge run by NZ-Asia Association Inc NZ and the NZ Diversity Action Programme.s
Keywords: Education; Education; Education (general).